Piling works of reinforced concrete pile / 'Ayuni Nadhirah Mohamad Yamin - Mohamad Yamin, Ayuni Nadhirah (Universiti Teknologi MARA, Perak, 2019)
This report describes the whole activities during my five months of industrial training at Fast Tech Builders Sdn. Bhd. The company handle construction work involving government agencies as well as the private sector. This report describes in detail the background of the company, inventory management, and information system, as well as activities conducted during the training period, issues encountered as well as constructive comments and suggestions on behalf of the organization. Foundation is an important structural element in determining the strength and stability of a building. It also plays a role in carrying the whole load and distributing the load to the ground. The base is the lowest in the building's structure that touches the ground.